Crystalline environment of luminescent Tb3+ ions embedded in indium tin oxide thin films: A DFT and crystal field analysis assessment - Serquen, E.; Lizárraga, K.; Enrique, L.A.; Bravo, F.; Mishra, S.; Llontop, P.; Venezuela, P.; Tessler, L.R.; Guerra Torres, J.A. (American Physical Society, 2025)
We assess the local symmetry and crystal environment of trivalent terbium ions embedded in an indium tin oxide matrix with bixbyite structure. The ${\mathrm{Tb}}^{3+}$ ions tend to substitute ${\mathrm{In}}^{3+}$ ions in two different cationic sites ($b$ and $d$). Density functional theory calculations suggest that the ${\mathrm{Tb}}^{3+}$ ions are mainly located at ${C}_{2}$ symmetry sites, relaxing selection rules and enabling electric dipole transitions, with the $^{5}D_{4}\ensuremath{\rightarrow}^{7}F_{2}$ transition being the most intense, providing a red color to the light emission. Photoluminescence emission spectrum under UV excitation at 83 K revealed 30 intra-$4f$ transitions, which were assigned to the $^{7}F_{J}$ ground multiplet of the ${\mathrm{Tb}}^{3+}$ ion. Crystal field analysis shows a strong alignment between calculated and observed energy levels, yielding a standard deviation of $\ensuremath{\sigma}=15.1\phantom{\rule{0.16em}{0ex}}{\mathrm{cm}}^{\ensuremath{-}1}$. We believe these results can help to understand the activation mechanisms of ${\mathrm{Tb}}^{3+}$ luminescent centers in transparent conductive oxides, as well as the potential to modulate ${\mathrm{Tb}}^{3+}$ emission color through its crystalline environment.
Keywords: Materials science; Luminescence; https://purl.org/pe-repo/ocde/ford#1.03.02